Globalization : the choices before us - Saul, John Ralston (2000)
Notes that there is nothing wrong with globalization, however, in the real world, it is not an absolute truth, because it is a theory that can take many forms. Suggests that the best way to navigate the complicated period ahead is to come back to the core force of democracy. Posits that from that basis it is possible to make sensible use of an ongoing technological revolution.